Gedung Sarinah: Memori dan Kontinuitas Modernisme Kota Jakarta - Neneng Churiah; Yulia Nurliani Lukito (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2023)
The physical change of Sarinah in 2022 captivates the residents of Jakarta. In the previous era, this building had lost its glory due to the lack of focused planning for renovations, especially when Jakarta's development accelerated with the presence of many new modern buildings. This writing uses a qualitative descriptive method with a historical approach. The analysis of architectural typology on the building facade is conducted by exploring the history to find out the origin of events, functions, and simple forms of a building. The aim is to provide an overview of the importance of giving more attention to the renovation of historic buildings. Changes in building facades can show a different identity from one urban space related to the political and socio-cultural context. Determination of cultural heritage status provides benefits for its preservation by increasing the potential of buildings to revive memories and the continuity of urban modernism.